2016
DOI: 10.1186/s12888-016-0860-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening value of the Center for epidemiologic studies – depression scale among people living with HIV/AIDS in Ho Chi Minh City, Vietnam: a validation study

Abstract: BackgroundDepression is believed to be under-diagnosed and under-treated in people living with HIV/AIDS (PLHIV). Early screening and referral to mental health services for treatment has been shown to enhance HIV patients’ health during the course of HIV treatment. A lack of psychiatric specialist services for PLHIV at outpatient clinics (OPC) in Vietnam leads to insufficient identification of depression. However, alternative approaches are available such as the use of screening scales. This study investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
0
23
1
Order By: Relevance
“…The prevalence of depression found in this study (26.2%) was relatively lower than that in previous studies targeting Vietnam’s HIV population, and using the same cut-off score for CES-D (36.5–78.0%) 6 , 18 , 19 . However, the prevalence in the present study was near that reported for Vietnam’s general population (24.3%) 49 .…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…The prevalence of depression found in this study (26.2%) was relatively lower than that in previous studies targeting Vietnam’s HIV population, and using the same cut-off score for CES-D (36.5–78.0%) 6 , 18 , 19 . However, the prevalence in the present study was near that reported for Vietnam’s general population (24.3%) 49 .…”
Section: Discussioncontrasting
confidence: 71%
“…CES-D is a widely used self-reporting scale for measuring depressive symptoms that participants experience 34 , 35 . There is strong evidence for both its reliability and validation in Vietnam’s HIV population, with Cronbach’s alpha of 0.81, and sensitivity and specificity of 79.8% and 83.0%, respectively, at the cut-off score of 16 19 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations